Fintech for Sharia Micro Finance Institution: Qualitative Analysis toward Utilization of Financial Technology in BPRS and BMT - Trimulato Trimulato (AL-FALAH : Journal of Islamic Economics, 2019)
Purpose:The articles aims to highlight the pattern of existing financial technology utilized by BPRS and BMT. Besides studying the pattern of Fintech, the article also effors to describe the growth of sharia micro financials--BPRS and BMT, as a main product of applied-FintechDesign/Methodology/Approach: Qualitative used consistenly as approach. To support that approach, analitical interpretation used to understand data.Findings: The results of this paper indicate that BPRS experienced good growth. Third Party Funds grew by 19.144% and financing grew by 14.862%, while the number of offices decreased by 0.222%. The BMT experienced 72.418 percent of receivables growth, 52.885 percent financing, and assets and placements grew below 40 percent. The pattern of financial technologhy (fintech) is very good for the development of sharia micro financial institutions such as BMT and BPRS. All existing fintech forms can be applied, such as crowfunding, peer to peer, payment and BMT and BPRS can serve as an intermediary for people who want to invest in sharia-compliant instruments/bussiness.Originality/Value: A set of novelty that can be stated from the article is that the study succesfully indentifacated in which the Fintech can be applied extensively in large typical financialmacro and micro financial industries.